Peran Mediasi Work Engagement pada Pengaruh Transformational Leadership dan Self Leadership Terhadap Job Performance - Mustikaningrum, Sari; Yulianti, Praptini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of transformational leadership and self-leadership on employee performance, with work engagement as a mediating variable, among employees of PT Toyota Astra Financial Services. A quantitative approach was used through a survey method, involving 112 respondents selected by purposive sampling. Data were analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM) based on first-order dimensions. The results show that self-leadership has a significant direct effect on employee performance, while transformational leadership does not have a direct effect. However, both variables indirectly affect performance through the mediation of work engagement. These findings highlight that work engagement is a key element that bridges leadership and self-directed behavior with performance outcomes. The practical implication of this study emphasizes the importance of enhancing work engagement through the development of leadership styles and self-leadership competencies.